Peran Guru Pendidikan Agama Islam dalam Pengembangan Sikap Ilmiah dan Literasi Sains Siswa - Sumirah Sumirah; Moh. Arsyad; Sukarno Sukarno (Journal of Educational Research, 2023)
This study reveals the teacher's role in cultivating scientific attitudes and student literacy in schools. The main problem discussed in this article is what is the role of Islamic religious education teachers in developing scientific attitudes and scientific literacy abilities of students at SMP Negeri 16 Jambi City. This article departs from descriptive qualitative research by collecting observations, interviews and documentation, with analytical techniques using the Miles and Huberman models. The results of the study show that the role of Islamic religious education teachers in developing students' scientific attitudes and scientific literacy abilities has been carried out well. Indicators of this include; students' ability to respond and solve problems, be more critical and curious, able to control themselves, build tolerance, and cooperate with each other when participating in learning activities. Students also have a better understanding of science concepts and are able to relate them to religious principles. Penelitian ini mengungkap peran guru dalam penanaman sikap ilmiah dan literasi siswa di sekolah. Permasalahan utama yang dibahas dalam artikel ini adalah bagaimana peran guru pendidikan agama Islam dalam pengembangan sikap ilmiah dan kemampuan literasi sains siswa di Sekoleh Menengah Pertama Negeri 16 Kota Jambi. Artikel ini berangkat dari penelitian kualitatif deskriptip dengan pengumpulan secara observasi, wawancara dan dokumentasi, dengan teknik analisis menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa peran guru pendidikan agama Islam dalam pengembangan sikap ilmiah dan kemampuan literasi sains siswa sudah dijalankan dengan baik. Indikator hal tersebut antara lain; kemampuan siswa dalam merespon dan memecahkan permasalahan, lebih kritis dan keingintahuan yang mendalam, mampu mengontrol diri, membangun sikap toleransi, dan saling kerjasama di saat mengikuti kegiatan pembelajaran. Siswa juga memiliki pemahaman yang lebih baik tentang konsep-konsep sains serta mampu menghubungkannya dengan prinsip-prinsip agama.